Reformulasi Pengaturan Upaya Rehabilitasi Terhadap Pelaku Tindak Pidana Kekerasan Seksual di Indonesia - Made Ryoko Aditya Arjana; Anak Agung Sagung Laksmi Dewi; Ketut Adi Wirawan (Jurnal Analogi Hukum, 2024)
Sexual violence is one of the most common criminal offenses in Indonesia. All types of sexual threats and coercion can be considered sexual violence. The type of rehabilitation provided to perpetrators of sexual violence can be used to prevent the return of such violence. The problem formulations of this research are: 1) How is the regulation of perpetrators of sexual violence who can be given rehabilitation efforts? 2) How is the form of reformulation of the regulation of rehabilitation efforts against perpetrators of sexual violence? The research method that the author uses in this research is normative research method. This study found that perpetrators of sexual violence who have sexual deviations, live in a residence, and have a health evaluation are likely to receive rehabilitation. The enactment of the Law on Sexual Violence reformulated the regulation of rehabilitation efforts against perpetrators of sexual violence. This law contains provisions on rehabilitating perpetrators of sexual violence crimes that were previously not regulated in the Criminal Code. The government is advised to improve the provisions in the law and encourage the community to participate in the implementation program.